The Common Law Mind of George Barton - McLachlan, Campbell (Victoria University of Wellington Law Review, 2012)
Dr George Barton’s remarkable life in the law exemplified two themes of general lasting importance. The first is the need to ensure that, in its progressive development, the New Zealand legal system takes full advantage of its membership of the wider common law family of legal systems. McLachlan argues that this is not merely a matter of optional comparative reference, pursuing a vague notion of transnational law. Rather, consideration of other common law authority is integral to legal reasoning in New Zealand and essential if the New Zealand legal system is to avoid the risk of insularity. The second general theme is the contribution that New Zealand can make to the practical achievement of international human rights, particularly within the same family of legal systems. McLachlan develops these two linked themes by reference to his personal experience of working with Dr Barton on Commonwealth legal matters over the last 30 years.